Organic Waste Management Behavior Through Cultivating Black Soldier Fly (BSF) - Rosdiana, Rosdiana (JURNAL INFO KESEHATAN, 2024)
Waste is our common problem because it is generated every day and throughout the year.  People’s behavior in throwing rubbish in any place and not caring about the environment can house an unpleasant atmosphere, especially the type of organic waste that causes an unpleasant odor. The aim is to find out the behavior of managing organic waste as feed in cultivating Black Soldier Flies (BSF) in RT 32 Bengkuring. The Qualitative research method with an action research (AR) approach. The research results show that the first stage, here is no organic waste management by residents in RT 32. Second stage, he implementation of socialization and training on BSF/maggot fly cultivation was welcomed by community shops, the government, and local residents. Third phase, most of the mothers were amused or disgusted to see maggots during training because they are shaped like caterpillars, so it is difficult to feed them organic waste. Besides that, it is difficult to get permission from the owners of houses or residential land that has not been used for a long time because their whereabouts are unknown to the owner. In conclusion, the knowledge of residents, community shops, and the local government increased after socialization and practice on how to manage organic waste through cultivating BSF flies. Behavior is low because not all residents dare to see, let alone touch and feed maggots.